The concentration and origins of carboxylic acid groups in oil paint - Baij, Lambert; Chassouant, Louise; Hermans, Joen J; Keune, Katrien; Iedema, Piet D (RSC advances, 2019)
Although the concentration of carboxylic acid (COOH) groups is crucial to understand oil paint chemistry, analytical challenges hindered COOH quantification in complex polymerised oil samples thus far. The concentration of COOH groups is important in understanding oil paint degradation because it drives the breakdown of reactive inorganic pigments to dissolve in the oil network and form metal carboxylates. The metal ions in such an ionomeric polymer network can exchange with saturated fatty acids to form crystalline metal soaps (metal complexes of saturated fatty acids), leading to serious problems in many paintings worldwide. We developed two methods based on ATR-FTIR spectroscopy to accurately estimate the COOH concentration in artificially aged oil paint models. Using tailored model systems composed of linseed oil, ZnO and inert filler pigments, these dried oil paints were found to contain one COOH group per triacylglycerol unit. Model systems based on a mixture of long chain alcohols showed that the calculated COOH concentration originates from side chain autoxidation at low relative humidity (RH). The influence of increasing RH and ZnO concentration on COOH formation was studied and high relative humidity conditions were shown to promote the formation of COOH groups. No significant ester hydrolysis was found under the conditions studied. Our results show the potential of quantitative analysis of oil paint model systems for aiding careful (re)evaluation of conservation strategies. Zinc complexation can be used to quantify the concentration of carboxylic acid groups in an oil painting.